Is the association between sleep and socio-emotional development mediated by weight in toddlers aged 12 to 36 months? - Duarte, Ana; Martins, Silvana; Lopes, Luís; Silva, Maria José; Augusto, Cláudia; Santos, Rute; Rosário, Rafaela (Frontiers in Psychology, 2023)
Introduction: Childhood is an important stage for socio-emotional development. Understanding the associations of lifestyle habits with the healthy development of social and emotional skills is crucial for better interventions early in life. This study aims to analyze the association between sleep and socio-emotional development in toddlers aged 12 to 36 months and examine whether weight mediated these associations. This is a provisional file, not the final typeset article Results: SE development was significantly associated with nighttime sleep duration even when adjusted for confounders (ᵦ=0.223; 95% CI: 0.001, 0.004 and ᵦ=0.168; 0.0003, 0.003; respectively). Sleep quality was not significantly associated with SE development, and the weight did not explain the associations between sleep and SE development.Conclusion: This study supports that sleep duration is directly associated with SE development in toddlers. From a public health perspective, sleep duration should be prioritized in intervention programs to improve socio-emotional development early in life.